Toxicity, Side Effects, and Furosemide Interactions in Therapy of Heart Failure Patients (Systematic Review) - Diniafelsa Wola; Noor Wijayahadi; Mochamad Ali Sobirin; Erwin Kresnoadi (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Furosemide as a diuretic loop is one of the main therapies given to heart failure patients with congestion, but in its use furosemide requires a lot of consideration related to toxicity, side effects, and drug interactions.Objective: To determine the toxicity, side effects and drug interactions of furosemide on heart failure patients.Methods: This research is a Systematic Review. Samples were obtained by searching for journals in the online databases of Pubmed, Scopus and Springer Link then adjusted to inclusion criteria and research questions. Data analysis was based on the PRISMA checklist, then searched for similarities and differences.Results: This study found the side effects of furosemide therapy in heart failure patients were: electrolyte disturbance such as: hyponatremia; hypokalemia; and hypomagnesemia, arrythmia, worsening renal function and worsening of AKI, hypotension, increase of plasma renin, and increased risk of fractures. No incidence of furosemid toxicity. The interaction of furosemide on heart failure patients may occur in several drugs like aspirin, digoxin, ACE-inhibitor, and bronchodilator.Conclusion: There is some side effect of furosemide and drug interactions occured in therapy of heart failure patients.Keywords: Furosemide, Toxicity, Side Effects, Interactions, Heart Failure.